Paroki Beraroma ‘Tungku Api’: Menuju Model Gereja Papua yang Kontekstual (Tanggapan atas Problematika Pastoral Paroki di Keuskupan Timika) - Emanuel Richardus Buang Lela (FOCUS, 2020)
This study focuses on a search for a contextual Church model in the Diocese of Timika. The purpose of this paper is to find patterns of preaching and parish services in pastoral care so that it is more contextual, actual, and relevant to the life situation of the faithful in the Diocese of Timika. The approach used in this research is a pastoral-cultur- al-symbolic study. This study finds that the terminology of the cultural symbol ‘Tungku Api’ can be used as a contextual and real means of preaching to answer contextual pas- toral issues in the Timika Diocese of Papua.